PENGGUNAAN METODE MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI KELAS XII MIPA 1 SMA NEGERI 2 PEKANBARU - Angreta Angreta (UIR Press, 2020)
This study aims to determine the increase of students learning outcomes through learning activities using Mind Mapping method in class XII MIPA 1 SMA Negeri 2 Pekanbaru. This research was conducted in July to September 2019. The subject was students of class XII MIPA 1 of SMA Negeri 2 Pekanbaru, totaling 36 students consist of 17 men and 19 women. This type of research is classroom action research. This research was conducted in two cycles for six meetings. Each meeting using the Mind Mapping method with consists of identifying the topic, planning the tasks to be studied, carrying out investigations, preparing final reports, presenting final reports, conclusions and evaluations. The research found that the usage of mind mapping method can improve the learning outcomes of class XII MIPA 1 SMA Negeri 2 Pekanbaru. The increasing was seen in the results of the first cycle with an average value of 84.13 and 92.66 in the second cycle. The percentage of students who pass the passing grade increase from 77.77% to 100%. Classroom action research with optimal usage of mind mapping method can improve learning outcomes in economic subject.